PENCATATAN NIKAH DALAM PENDEKATAN MASLAHAH - SULASTRI CANIAGO (Institut Agama Islam Negeri Batusangkar, 2016)
Marriage is basically the main element in the establishment of sakinah, mawaddah and rahmah family. Consequently, to realize such expected family, fixed laws are needed. The implementation of such laws in marriage is aimed at maintaining rights, ….. and responsibilities of the family members in order to realize everlasting and qualified family which is suitable with marriage purposes. Therefore, administrating marriage which has been stated in laws is becoming obligation to carry out. If it is viewed further from maslahah approach, administrating marriage can be included into maslahah in the level of dharuriyah in which such maslahah must be fulfilled unless it will jeopardize the existence of nasab.Kata kunci: pencatatan, nikah, maslahah